The Portable Hometown: Social Networks, Moral Space, and the Making of Nostalgia among Rural Migrants in a Jiangxi Town - Huang, Hui (Transactions on Social Science, Education and Humanities Research, 2026)
Existing scholarship affirms that nostalgia matters for rural revitalization, yet treats it either as a self-evident concept or as a purely psychological emotion, leaving both its social genesis and its pathway to rural reconstruction a black box. Drawing on two months of fieldwork and twenty in-depth interviews with fifteen rural-to-urban migrants from Zhaochen, a relatively isolated town in Jiangxi Province, this study reconceptualizes nostalgia as an overdetermined dependence on a kin–native-place social network—a "portable hometown" that migrants carry with them. Three mutually embedded mechanisms produce and sustain this dependence: the deep embedding of the network in migrants' livelihood practices; a family-centred moral space that lowers the cost of maintaining and reactivating ties; and the interaction of individual and significant others' life courses. The paper then argues that the way nostalgia drives rural reconstruction continues its genesis rather than forming a separate process: acts such as repairing houses, donating, and restoring ancestral halls are a "performance of identity" that copes with the anxiety nostalgia generates. Urban integration and rural revitalization thus emerge as two sides of one problem.
Keywords: Nostalgia; rural-to-urban migrants; social networks; identity; rural revitalization.